PERLINDUNGAN HUKUM KONSUMEN TERHADAP PEREDARAN PRODUK PANGAN KEMASAN TANPA TANGGAL KADALUWARSA DAN KEMASAN CACAT (STUDI KASUS PUTUSAN NOMOR 66/Pid.Sus/2017/PN. Ktb) - Grace Riana Yudistira; Anna Maria Tri Anggraini (Jurnal Hukum Adigama, 2020)
Food is a basic human needs that is necessary to be fulfilled. Consumer when consume food product must be considered about the basic ingredients are contained, nutrient content, how the food process is, storage, packaging, and the expire date of the product. On the end of 2017, there was a case about a Mini Market that sold some products without an expire date on the food packaging and the food packaging were damaged. Food Packaging is a material that is used for wrapped the product, whether get in touch with the product directly or not. Good packaging purpose are to protect the food and prevent the damage. Therefore, it is very important to have an expire date and have a good packing. Expired means time has passed or time is running out of time. Just as determined and when the expired food was consumed it can harm the Consumer's health. The Author in this study is using a method that based for academics needs. The author analyzed that the seller was violating regulations that are prohibited for business seller and violating consumer’s rights. This case is against the regulation of the consumer protection based on the Law number 8 of 1999. The consumer protection purpose was made to create a consumer protection that contained legal certainly elements and opened information.